Simultaneous Determination of Five Active Ingredients in Huangshixiangsheng Pills by HPLC - Cheng, Weiming; Gao, Jie; Huang, Qinwei; Shi, Bei; Zhang, Wenting (Asian Journal of Chemistry, 2013)
To establish an HPLC method for the simultaneous determination of five active ingredients in a famous Chinese clinical complex prescription. HPLC conditions included Hypersil-C18 column (4.6 mm × 250 mm, 5 μm) and the mobile phase was a mixture of acetonitrile and 0.1 % phosphoric acid for gradient elution. The flow rate was 1 mL/min and the column temperature was at 30 ºC. Five active ingredients had good linear relationships: Aloe-emodin in the range of 0.0081-0.4045 μg (R2 = 0.9997), rhein in the range of 0.0065-0.3255 μg (R2 = 0.9997), emodin in the range of 0.0124-0.6220 μg (R2 = 0.9997), chrysophanol in the range of 0.0138-0.6910 μg (R2 = 0.9999) and physcion in the range of 0.0032-0.1615 μg (R2 = 0.9994). Their average recoveries were 99.1 % (RSD = 1.2 %), 98.6 % (RSD = 1.7 %), 97.4 % (RSD = 1.4 %), 97.4 % (RSD = 2.6 %) and 97.0 % (RSD = 0.6 %), respectively. This method was steady with high precision and good repeatability and could be used for the determination of the five active ingredients and quality control of Huangshixiangsheng pills.